(untitled) (Journal of Applied Learning and Teaching, 2018)
There has been much debate in Higher Education (HE) about the use of innovative technologies to enhance student learning. However, while technology alone may not have fundamentally changed teaching practices (Henderson, Selwyn & Aston, 2017), students report how several technologies and applications benefit their learning, research and collaborative activities (Henderson et al., 2017). Over the past 26 years, Kaplan and University College Dublin’s (UCD) College of Business’ Centre for Distance Learning (CDL) offer a wide range of undergraduate and postgraduate programmes to students in Singapore. Drawing upon a concise analysis of relevant literature and theoretical frameworks in the context of student learning and engagement, the author examines how Kaplan’s state of the art collaborative learning environment, the Synergy Pods, can facilitate more effective and efficient student learning, assessment, feedback and engagement.